Research groups: together we reach further - Quispe-Salcedo, Angela (2021)
In recent years, the effort to promote the development of scientific research in the country has been palpable, especially within the different higher education institutions. Since the beginning of the university reform, the guidelines defined by the National Council for Science, Technology and Technological Innovation (Concytec) have contributed to the vertiginous advance of the scientific production of universities and other training centers, which has changed the paradigm of “university that teaches” to that of “university that investigates”